Characterization and outcome of post-transplant lymphoproliferative disorders within a collaborative study - Lückemeier, Philipp; Radujković, Aleksandar; Holtick, Udo; Kurch, Lars; Monecke, Astrid; Platzbecker, Uwe; Herling, Marco; Kayser, Sabine (Frontiers in oncology, 2023)
Background: Post-transplant lymphoproliferative disorders (PTLD) are heterogeneous lymphoid disorders ranging from indolent polyclonal proliferations to aggressive lymphomas that can arise after solid organ transplantation (SOT) and allogeneic hematopoietic transplantation (allo-HSCT). Methods: In this multi-center retrospective study, we compare patient characteristics, therapies, and outcomes of PTLD after allo-HSCT and SOT. Twenty-five patients (15 after allo-HSCT and 10 after SOT) were identified who developed PTLD between 2008 and 2022. Results: Median age (57 years; range, 29-74 years) and baseline characteristics were comparable between the two groups (allo-HSCT vs SOT), but median onset of PTLD was markedly shorter after allo-HSCT (2 months vs. 99 months, P<0.001). Treatment regimens were heterogeneous, with reduction of immunosuppression in combination with rituximab being the most common first-line treatment strategy in both cohorts (allo-HSCT: 66%; SOT: 80%). The overall response rate was lower in the allo-HSCT (67%) as compared to the SOT group (100%). Consequently, the overall survival (OS) trended towards a worse outcome for the allo-HSCT group (1-year OS: 54% vs. 78%; P=0.58). We identified PTLD onset ≤150 days in the allo-HSCT (P=0.046) and ECOG >2 in the SOT group (P=0.03) as prognostic factors for lower OS. Conclusion: PTLD cases present heterogeneously and pose unique challenges after both types of allogeneic transplantation.
Gesehen am 23.08.2023